SARS-CoV-2 immune responses in patients with multiple myeloma and lenalidomide maintenance therapy - Martac, Ioana; Beer, Sina A.; Schenk, Aileen; Ahmad, Osama; Maier, Claus-Philipp; Demirel, Gülay; Preuß, Beate; Klein, Reinhild; Stanger, Anna M. P.; Besemer, Britta; Hensen, Luca; Lengerke, Claudia (Frontiers in Immunology, 2024)
IntroductionMultiple myeloma (MM) is an uncontrolled plasma cell proliferation in the bone marrow, leading to immune dysregulation with impaired humoral immune responses. Conversely, cellular-based responses play a vital role in MM patients. However, the extent and duration of cellular-induced protection remain unclear to date. Here, immunomodulatory drugs (IMiDs) like Lenalidomide (Lena) become interesting, as they may have stimulatory effects on T-cell functioning.MethodsIn this study we investigated immune responses elicited by COVID-19 vaccine or infection comparing 43 healthy volunteers (avg. 35y, 72.1% female, 81.4% previously COVID-19 infected), with 41 MM patients under Lena maintenance therapy (avg. 63.8y, 51.2% female, 61% previously COVID-19 infected). Humoral responses to SARS-CoV-2 spike (S), spike-RBD, and nucleocapsid (N) were measured via ELISA in subjects’ plasma. Freshly isolated PBMCs, incubated with SARS-CoV-2 peptides (N, S), activation induced marker (AIM) assays and flow cytometry, allowed us to assess cellular responses (CD8+ T, T(F)H: CD4+ T (follicular) helper).ResultsWhereas healthy controls showed significant better humoral responses (N IgA p<0.001), T cell responses were robust in the MM group (higher S-act. TH, p<0.001). Stratified by COVID-19 status, the MM group showed higher N-act. TH (p=0.03). These results were unchanged comparing a Lena intake with Lena break around vaccination.DiscussionTaken together, MM patients under Lena therapy exhibit weakened antibody production but present a robust T cell response following SARS-COV-2 infection or vaccination. Our results highlight the importance of vaccination in this subgroup and moreover, argue against a Lena intake break around the time of vaccination.